Safety assessment of the substance phosphorous acid, triphenyl ester, polymer with alpha‐hydro‐omega‐hydroxypoly[oxy(methyl‐1, 2‐ethanediyl)], C10–16 alkyl esters, for use in food contact materials. (16th May 2019) - ,; Silano, Vittorio; Barat Baviera, José Manuel; Bolognesi, Claudia; Brüschweiler, Beat Johannes; Chesson, Andrew; Cocconcelli, Pier Sandro; Crebelli, Riccardo; Gott, David Michael; Grob, Konrad; Lampi, Evgenia; Mortensen, Alicja; et al.
Abstract: The EFSA Panel on Food Contact Materials, Enzymes and Processing Aids (CEP Panel) assessed the safety of the substance 'phosphorous acid, triphenyl ester, polymer with alpha‐hydro‐omega‐hydroxypoly[oxy(methyl‐1, 2‐ethanediyl)], C10–16 alkyl esters', obtained by reaction of ■■■■■, when used as an additive at up to 0.2% w/w in high impact polystyrene. The plastic, in the form of films and articles, is intended for contact with aqueous, acidic, low‐alcohol and fatty foods for long‐term storage at room temperature and below, after hot‐fill and/or heating up to 100°C for up to 2 h. Based on genotoxicity tests with negative results, the Panel considered that there is no evidence of mutagenicity and chromosomal damage of the substance and its phosphate form. From a repeated dose 90‐day oral toxicity study in rats, the Panel identified the no‐observed‐adverse‐effect level as 50 mg/kg body weight (bw) per day. No effects of induced delayed neurotoxicity in hens were observed. Migration from high impact polystyrene containing the substance at 0.2%, measured through the phosphorous content of the substance, reached 0.001 mg/kg in 10% ethanol and 0.1 mg/kg in 95% ethanol. Migration into acidic food/simulant is expected to be below 0.001 mg/kg. Regarding the oligomers and other reaction/degradation products detected, the phosphorous‐containing substances were adequately represented in the toxicity experiments conducted. Those not containing phosphorous were hydrolysis products either listed in Regulation (EU) 10/2011 and their estimated worst‐case migrations were well below their respective specific migration limits (SMLs) or no alerts for genotoxicity were noted. Overall, the CEP Panel concluded that the substance 'phosphorous acid, triphenyl ester, polymer with alpha‐hydro‐omega‐hydroxypoly[oxy(methyl‐1, 2‐ethanediyl)], C10–16 alkyl esters' does not raise a safety concern for the consumer if it is used at up to 0.2% w/w in high impact polystyrene materials and articles and its migration does not exceed 0.05 mg/kg food.